Dysregulated zinc homeostasis and microadenomas in the anterior pituitary: pathological insights into suicide risk - Tendilla-Beltrán, Hiram; Aguilar-Alonso, Patricia; Hernández-González, Carlos Alejandro; Baltazar-Gaytán, Eduardo; Orduña, Ana A.; Nicolini, Humberto; García-Dolores, Fernando; Flores, Gonzalo (Frontiers in Psychiatry, 2024)
Background: Suicide is a significant public health problem influenced by various risk factors, including dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis. Zinc (Zn), essential for pituitary function in hormone synthesis and release, has been linked to suicide, with studies noting reduced serum levels and altered brain transport mechanisms. Despite Zn's crucial role in pituitary function and its involvement in suicidal behavior, information on pituitary Zn in suicide is scarce.Tumor cells modify Zn dynamics in tissues, and a previous report suggests microadenomas in the anterior pituitary as a risk factor for suicide.Methods: Histopathological analysis with hematoxylin-eosin stain and histochemical techniques to assess Zn homeostasis were carried out on anterior pituitary postmortem samples from 14 suicide completers and 9 non-suicidal cases.Results: Pituitary microadenomas were identified in 35% of suicide cases and none in the non-suicidal cases. Furthermore, compartmentalized Zn (detected via dithizone reactivity), but not free Zn levels (detected via zinquin reactivity), was lower in the suicide cases compared to the non-suicidal group.This is the first report of a potential association between disrupted Zn homeostasis and microadenomas in the anterior pituitary as a feature in suicide and provides critical insights for future neuroendocrine Zn-related research.